Implementing the teaching of transformative Learning to improve university students’ reading Self-efficacy in China - Jiaquan Wang; Wendy Hiew; Suyansah Swanto (Global Academic Excellence (M) Sdn Bhd (GAE), 2022)
This paper aims to investigate the implementation of the teaching of transformative learning to improve students’ reading self-efficacy at university in China. The study used a questionnaire on reading self-efficacy as the research instrument to survey 85 non-English students’ reading self-efficacy. A comparison of the pre- and post-test mean scores of the students reading self-efficacy using Wilcoxon Signed Ranks Test indicated a significant difference with the introduction of the teaching of transformative learning in improving the students’ reading self-efficacy. The three main features of the teaching of transformative learning include (1) using critical reflection to change students’ thinking and improve their self-efficacy, (2) using rational discourse to change students’ psychological state, and (3) using peaceful and equal classroom atmosphere to enhance dialogue and students’ self-efficacy to build an environment that is congruent with the learners’ learning expectancy.